La sobreprotección y su incidencia en el desarrollo psicomotriz de los niños y niñas de preparatoria primer grado de educación general básica de los centros educativos “la consolación” y “Tomás Rendón” de la ciudad de Cuenca. Periodo lectivo 2014 – 2015 - Valencia Vinces, Marisela Del Consuelo (2015)
This research was part of an analytical, descriptive and explanatory study of "LA SOBREPROTECCIÓN Y SU INCIDENCIA EN EL DESARROLLO PSICOMOTRIZ DE LOS NIÑOS Y NIÑAS DE PREPARATORIA PRIMER GRADO DE EDUCACIÓN GENERAL BÁSICA DE LOS CENTROS EDUCATIVOS “LA CONSOLACIÓN” Y “TOMAS RENDÓN" DE LA CIUDAD DE CUENCA. PERIODO.LECTIVO2014- 2015", the same that was developed according to the Regulation of Academic System of the National University of Loja. The central problem of my investigation finds to him the following question: ¿What affects the en Overprotection psychomotor development of children in the first year of basic education schools "Consolation" and "Thomas Rendon" of the city of Cuenca? 2014-2015 academic year? Previously the overall objective was formulated: To determine the incidence of over-the Psychomotor Development of children in First Grade of Basic General Education The following methods were used for carrying out this work: - Deductive, Analytical - Scientific, Inductive Synthetic, descriptive and statistical model; techniques and instruments were: Survey of parents of children in First Grade School Basic General Education schools "Consolation" and "Thomas Rendon" City of Cuenca to establish the overprotection of children and girls and Otzeretsky Test applied a children High School First Grade of Basic General Education schools "Consolation" and "Thomas Rendon" Cuenca City attending the Schools, to assess psychomotor development Application Survey to parents it was found that: Parents of children High School First Grade of Basic General Education schools "Consolation" and "Thomas Rendon" of the city of Cuenca a higher percentage not overprotect their children but if a smaller percentage overprotection. Parents are overprotective attitudes with their children. Children assume attitudes that correspond to a overprotected child when his desires are opposed. According to the results of the application of the Otzerestky test it demonstrated that a major percentage of children’s and young have a satisfactory psychomotor development and minorpercentage unsatisfactory.